«Հաղորդությունը» Թորոս սարկավագի և Թորոս Տարոնացու մանրանկարներում - Բարսեղյան, Լուսինե
The Eucharist was instituted by Jesus Christ at the Last Supper and this event found its pictorial expression in art. The scene of the Last Supper is presented as a historical event with Christ and the apostles seated at the table, where the future betrayal is particularly emphasized, while the images of the Eucharist show the liturgical interpretation and emphasize its symbolic meaning. In the scene of the Communion of the Apostles, Christ assumes the form of a priest, the supper table is transformed into an altar, and the apostles receive communion as true believers. In the narrative cycle of Armenian manuscripts, the Communion of the Apostles is not widespread and occurs rarely. In miniatures, the image appears from the 13th century and remains until the 17th century. It is noteworthy that in the rich manuscript heritage of the numerous scriptoria of Vayotsʻ Dzor, the scene depicted only in three miniatures. The first is a separate fragment from a valuable manuscript created by T’oros the Deacon in 1311, probably in Gladzor. The other two were painted by T’oros Taronatsʻi in Gladzor: one is in the manuscript dated 1321 and commissioned by Princess Vakhakh, and the other is in the Gospel dated 1323 and commissioned by Esayi Nchʻetsʻi. Евхаристия была установлена Иисусом Христом на Тайной Вечере. Это событие нашло свое выражение в изобразительном искусстве. Сцена Тайной вечери рисуется как конкретное историческое событие, с сидящими за столом Христом и апостолами, где особенно подчеркивается будущее предательство. В то же время изображения Евхаристии дают литургическую интерпретацию этой сцены и подчеркивают ее символическое значение. В сцене “Причащение Апостолов” Христос принимает облик священника, стол для трапезы превращается в алтарь, а апостолы причащаются в образе верующих церкви. В армянских рукописях “Причащение Апостолов” не имеет широкого распространения и встречается довольно редко. В иллюстрированных миниатюрах изображение появляется с XIII века и сохраняется до XVII века. Примечательно, что в богатом рукописном наследии многочисленных скрипториев Вайоц Дзора композиция “Причащение апостолов” известны лишь в трех миниатюрах. Первая – это отдельный фрагмент из ценной рукописи, созданной Торосом Дьяконом в 1311 году, вероятно, в Гладзоре. Следующие две работы выполнены в Гладзоре Торосом Таронаци: одна из рукописи 1321 года, заказанной княгиней Вахах, другая из Евангелия 1323 года, заказчиком которого является Есаи Нчеци.
Keywords: Արվեստ; Մանրանկարչություն